PENGHAKIMAN BERDASARKAN PERBUATAN DI ROMA 2:1-16 - Valentino, Fabio (Jurnal Amanat Agung, 2019)
Tema “Penghakiman berdasarkan perbuatan” yang muncul di Roma 2:1-16 telah menimbulkan berbagai perbedaan pandangan di kalangan para ahli. Perdebatan ini disebabkan tema “Penghakiman Berdasarkan Perbuatan” seolah-olah bertentangan dengan pernyataan Paulus mengenai “Pembenaran oleh iman” dan perbuatan dapat menjadi penentu keselamatan. Tulisan ini berusaha memberikan sumbangsih untuk memahami “Pembenaran oleh iman” melalui kerangka soteriologi Paulus. Abstract: The theme of "Judgment according to Works" that appears in Romans 2: 1-16 has given rise to different views among experts. This debate is caused by the theme " Judgment according to Works " as if it contradicts with Paul’s statement about "Justification by faith" and works can be determinants of salvation. This paper attempts to contribute to understanding this theme through Paul’s soteriological framework.